VALIDITY AND RELIABILITY OF THE STUDENT WORK READINESS SCALE - Sultoni Sultoni; Imam Gunawan; Anjar Agus Firawati; Anggraeni Cahyaningtyas (Universitas Negeri Malang, 2022)
Abstract: Work readiness can be defined as the extent to which individuals are seen to possess the attitudes and characteristics necessary for future success in the workplace. This study aims to assess the Student Work Readiness Scale. Five dimensions and twenty-one items are arranged to measure the construct of student work readiness. The questionnaire survey was administered to 151 students at Universitas Negeri Malang. The correlation of Pearson’s Product Moment to test validity and Cronbach’s Alpha to test reliability. According to the results, 21 items possessed a high level of validity and reliability. Keywords: student work readiness, validity, reliability, questionnaire, correlatio